Coptic culture and community : daily lives, changing times - Ayad, Mariam F., (The American University in Cairo Press, 2024)
"This volume brings together leading experts from a range of disciplines to examine aspects of the daily lived experiences of Egypt's Coptic Christian minority from late Antiquity to the present. In doing so, it serves as a supplement and a corrective to institutional or theological narratives, which are generally rooted in studying the wielders of historical power and control. Studies in Coptic Culture and Community reveals the humanity of the Coptic tradition, giving granular depth to how Copts have lived their lives through and because of their faith for two thousand years. The first three sections consider in turn the breadth of the daily life approach, perspectives on poverty and power in a variety of different contexts, and matters of identity and persecution. The final section reflects on the global Coptic diaspora, bringing themes studied for the early Coptic Church into dialog with Coptic experiences today. These broad categories help to link fundamental questions of socio-religious history with unique aspects of Coptic culture and its vibrant communities of individuals."--